Etching performance of silicon wafers with redesigned etching drum - Dolah, Rozzeta (2006)
Etching process involves various chemical reactions and reflects significantly on silicon wafer quality. This master project addresses the major problem on wafers during etching that is wafer removal distribution throughout etching drum compartment. The etching drum has been redesigned to overcome the lower removal problem at the end of each compartment. The characteristics of the end wafers are compared with other wafers in the compartment to study the etching difference that leads to this problem. Etching parameters are then evaluated in order to optimize the etching process in conjunction with the use of this new drum. For optimization purpose is by applying Design of Experiment (DOE) with full factorial design is employed. Etching factors namely the bubbling flow rate, wafer rotation, and etchant temperature had been varied in 11 runs in the DOE. The responses studied etching removal, total thickness variation (TTV) and wafer brightness. It is found that etchant temperature gives major a impact on all three responses stated above. The etchant temperature is the main effect factor and significantly affects TTV. Additionally, the etchant temperature and bubbling flow rate provide interaction effect on both the etching removal and wafer brightness. A higher bubbling flow rate is required to ensure etching removal and brightness within specification. Besides studying these three responses, the wafer surface after etching is additionally analyzed using ADE Infotool software which captures the etched profile and its thickness. From the ADE result, it again indicates that a higher temperature contributes to a more concave shape of etched wafer, thus resulting in higher TTV sending the wafers to be out of specification. Finally, the optimum condition is tested on a final run utilizing all the four compartments. The uniformity without lower removal at the end compartment is observed in removal distribution graph. The new drum design performance is enhanced with the optimized value of bubbling flow rate, etchant temperature and wafer rotation to achieve the best removal distribution.